The Effect of Therapeutic Drug Monitoring on Safety and Efficacy of Voriconazole in Invasive Fungal Infections: A Randomized Controlled Trial - Park, Wan Beom; Kim, Nak-Hyun; Kim, Kye-Hyung; Lee, Seung Hwan; Nam, Won-Seok; Yoon, Seo Hyun; Song, Kyoung-Ho; Choe, Pyoeng Gyun; Kim, Nam Joong; Jang, In-Jin; Oh, Myoung-don; Yu, Kyung-Sang (Clinical infectious diseases, 2012)
Background. Blood levels of voriconazole, a first line therapy for invasive aspergillosis, may correlate with adverse events and treatment response. However, no randomized controlled studies have been conducted to evaluate the clinical utility of routine therapeutic drug monitoring (TDM) of voriconazole. This study aimed to determine whether routine TDM of voriconazole reduces drug adverse events or improves treatment response in invasive fungal infections. Methods. This was a randomized, assessor-blinded, controlled, single center trial. One hundred ten adult patients were randomly assigned to TDM or non-TDM groups. In the TDM group, voriconazole dosage was adjusted (target range, 1.0–5.5 mg/L) according to the serum trough level measured on the fourth day after initiation of voriconazole. The non-TDM group received a fixed, standard dosage. Voriconazole-related adverse events were monitored, and treatment response was assessed three months after the initiation of therapy. Results. Baseline characteristics including the CYP2C19 genotype were comparable between the two groups. While the incidence of adverse events was not different between the TDM group and the non-TDM group (both 42%; P = .97), the proportion of voriconazole discontinuation due to adverse events was significantly lower in the TDM group than in the non-TDM group (4% vs 17%; P = .02). A complete or partial response was observed in 81% (30 of 37) of patients in the TDM group compared to 57% (20 of 34) in the non-TDM group (P = .04). Conclusions. Routine TDM of voriconazole may reduce drug discontinuation due to adverse events and improve the treatment response in invasive fungal infections. Clinical Trial Registration. NCT00890708.